MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA DALAM MENGURAI TEKS BACAAN MELALUI DISKUSI KELOMPOK PADA SISWA KELAS VI - ISIH SUBEKTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This Classroom Action Research aims to improve the learning process to improve Indonesian language learning outcomes in parsing Reading Texts through group discussions for sixth graders at SDN Ngeposari II Kapanewon Semanu, Gunungkidul Regency. This research was conducted from August 2021 to October 2021. Through group discussions by implementing four activity steps: Planning, Implementation, Observation and Reflection. In the second cycle of assessment scores, it was shown that the students' ability in learning Indonesian about parsing reading texts through group discussions was able to increase students' competence in learning Indonesian. It was proven that the second cycle score was 86.87, an increase of 21.41 when compared to the first cycle of 65.46 because the results in the second cycle were already showed a very good improvement and had exceeded the researcher's expectations of 80 with a final score of 86.87, the study was stopped with the criteria of a